The challenge of deep-level mining in South Africa (Presidential Address) - H. Wagner (The Southern African Institute of Mining and Metallurgy, 1986)
The discovery of the gold-rich Main Reef Group of reefs on the farm Langlaagte in 1886 marked the opening of the richest and most extensive goldfield in history. Mining of the narrow reefs progressed from the outcrops to more than 3,5 km, and has made South Africa the foremost mining country in the world. Changes in the political and socio-economic climate create a new challenge to the gold-mining industry. The most significant of these is the emergence of Black trade unions, with their demands for higher wages, improved safety, job advancement, and abolition of discriminatory legislation. Industrial conflicts on gold mines have risen significantly in the past ten years, and are likely to continue in the future, although the causes of these conflicts may change. Events largely outside the control of the gold-mining industry, such as the improved dollar price for gold and the depreciation of the value of the rand relative to major currencies, have enabled the industry to meet the demands for higher wages and to narrow the wage gap. However, labour productivities have improved insignificantly and are a cause of major concern for the future development of the industry. Continued pressure in the industrial-relations area, the inflation of working costs, and the extension of mining operations to greater depths and more difficult areas create major challenges to mine managements and mining engineers. Significant improvements in mining technology, environmental control, and safety will have to be made to ensure the long-term survival of the industry. The unavoidable introduction in deep gold mines of mechanization on a larger scale to meet the requirements of higher labour productivities and a better and safer underground environment will have a major impact on the cost and management structure of these mines. Engineering will assume a more important role on deep gold mil1es, and management styles and structures will have to be adapted to accommodate these changes. The supply of suitably qualified engineers, technicians, and artisans will be a crucial factor controlling the rate of technological change. The industry is well-geared through its Group system to meet these challenges, and to benefit from the experience gained in the operation of highly mechanized mines. However, changes take time to implement and there is very little time left.